Microleakage of Different Adhesive Systems in Primary Molars Prepared by Er: YAG Laser or bur - EREN GİRAY, FİGEN; KALYONCU, IŞIL ÖZGÜL (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2018)
Background and aim: This study aimed to examine the microleakage of class V cavities of primary molars prepared by either a conventional dental bur or Er:YAG laser and one of two different adhesive systems. Methods: A total of 50 tooth samples from primary molars were used in this study. They were randomly assigned into five experimental groups of 10 samples each, according to the cavity preparation technique and the type of adhesive system applied to the cavities. Following cavity preparation, etching, bonding, and filling steps, samples were dyed using basic fuchsine and were sectioned longitudinally in buccolingual direction. Percentages of dye penetration at gingival and occlusal margins were calculated for each group. Results: Overall, microleakage scores of gingival margins were significantly higher than those of occlusal margins (P < 0.001). The group that underwent laser preparation, laser etch, and self-etch bonding procedures had worse microleakage scores for gingival margins. However, all groups had similar occlusal scores (P 0.05). Conclusion: Self-etch bonding systems and cavity preparation with Er:YAG laser may be an alternative to conventional restoration of primary molars with compomers. Further studies are warranted to fully elucidate the effect of laser-based etching techniques in cavities prepared by laser.
Keywords: Adhesive system; cavity preparation; microleakage; primary molar; PRIMARY TEETH; COMPOSITE RESTORATIONS; ERYAG LASER; IN-VITRO; CAVITIES; IRRADIATION; DENTIN